Artesunate Affects T Antigen Expression and Survival of Virus-Positive Merkel Cell Carcinoma - Sarma, Bhavishya (Cancers (Basel), 2020)
Merkel cell carcinoma (MCC) is a rare and highly aggressive skin cancer with frequent viral etiology. Indeed, in about 80% of cases, there is an association with Merkel cell polyomavirus (MCPyV); the expression of viral T antigens is crucial for growth of virus-positive tumor cells. Since artesunate—a drug used to treat malaria—has been reported to possess additional anti-tumor as well as anti-viral activity, we sought to evaluate pre-clinically the effect of artesunate on MCC. We found that artesunate repressed growth and survival of MCPyV-positive MCC cells in vitro. This effect was accompanied by reduced large T antigen (LT) expression. Notably, however, it was even more efficient than shRNA-mediated downregulation of LT expression. Interestingly, in one MCC cell line (WaGa), T antigen knockdown rendered cells less sensitive to artesunate, while for two other MCC cell lines, we could not substantiate such a relation. Mechanistically, artesunate predominantly induces ferroptosis in MCPyV-positive MCC cells since known ferroptosis-inhibitors like DFO, BAF-A1, Fer-1 and β-mercaptoethanol reduced artesunate-induced death. Finally, application of artesunate in xenotransplanted mice demonstrated that growth of established MCC tumors can be significantly suppressed in vivo. In conclusion, our results revealed a highly anti-proliferative effect of the approved and generally well-tolerated anti-malaria compound artesunate on MCPyV-positive MCC cells, suggesting its potential usage for MCC therapy.